Respuestas

2012-05-06T07:05:44+02:00

(0.1x - 0.3)2.5- (0.4+0.2x)0.3 + 1.1x =0.8 - (0.3 - 4.3x) 0.3

0.25x-0.75- (0.12+0.06x)+1.1x=  0.8-(0.09-1.29x)

0.25x-    0.75  -    0.12    -    0.06x   +   1.1x    =  0.8    -    0.09  +   1.29x

0.25x   -  1.29x - 0.06x + 1.1x  =  +  0.8 - 0.09 +     0.12 +   0.75 

 

+0.25x   -  1.29x - 0.06x + 1.1x  =  +  0.8 - 0.09 +     0.12 +   0.75  ahora sigo 

+1.35x  -1.35x   =  +1.67- 0.09

+1.35x  -1.35x =  +165.24

2012-05-06T07:11:02+02:00

solo multiplica separa ternimos con x    y los otros sin la variable  y listo te da 

x= 63.2